Environmentally sustainable diets and human health - Nutritional adequacy, disease risk, and mortality - Stubbendorff, Anna ; 0000-0001-9851-6213 (Lund University, Faculty of Medicine Doctoral Dissertation Series, 2026)
Introduction: Food systems strongly influence both human and planetary health. Unhealthy diets are major risk factors for chronic disease and mortality, while food production contributes substantially to greenhouse gas emissions (GHGE), and other negative environmental impacts. Adopting more sustainable dietary patterns, such as the EAT-Lancet diet, has been proposed as part of the solution, but uncertainties remain regarding their long-term health effects, nutri-tional adequacy, and optimal methods for assessment. Aim: The aim of this thesis was to examine associations between environmentally sustainable diets, nutritional adequacy, and major health outcomes, with a focus on mortality, cardiovascular disease, diabetes, and micronutrient intake and status. Methods: The analyses were mainly based on the Malmö Diet and Cancer Study, including about 26,000 adults followed for up to 30 years. Dietary intake was assessed using a validated diet history method combining a 7-day food diary, questionnaire, and interview. Health outcomes were retrieved from national registers. Nutrient adequacy was evaluated using both dietary data and blood biomarkers. Life cycle assessment (LCA) was used to estimate dietary GHGE, and adherence to the EAT-Lancet diet was assessed using dietary scores. Results: Higher adherence to the EAT-Lancet diet was associated with lower risks of mortality, reduced stroke risk, and lower GHGE. Lower dietary GHGE were most consistently associated with decreased risk of diabetes, while associations with mortality were weaker and partly non-linear. Diets with lower environmental impact were generally compatible with adequate micronutrient intake and status and were sometimes linked to nutritional benefits, such as a reduced risk of folate deficiency, though a slightly higher risk of anaemia was observed. Conclusion: Environmentally sustainable diets can promote health, reduce mor-tality, and do not substantially increase the risk of micronutrient deficiencies. These findings underscore the co-benefits of aligning nutrition and climate poli-cies and support the integration of sustainability into dietary guidelines.
Keywords: Sustainable diets; Climate friendly diets; Climate change; Sustainable development; Non-communicable disease; Micronutrients; EAT-Lancet diet; Nutrition; Mortality